Progress in the system of advanced training of research and teaching staff in Ukraine in the 1970s – early 21st century: analysis criteria - Babakina, O. (Problems of Engineer-Pedagogical Education, 2021)
The article identifies the criterional apparatus of the analysis and evaluation of the progress in the system of advanced training of research and teaching staff in Ukraine in the period from the 1970s until the early 21st century. Scientific methods of analysis, generalization, description and comparison were used to determine the criteria. The author argues that the criteria for analysis and evaluation of the progress in the system of advanced training of research and teaching staff in Ukraine in the 1970s – early 21st century is a set of characteristics based on understanding the dynamics of the processes during the chosen period. Their indicators are clear evidence through which it is possible to analyze and evaluate the progress in the system of advanced training of research and teaching staff in Ukraine (the 1970s – early 21st century). Based on the analysis of scientific achievements, the author identified the criteria for the analysis and evaluation of the progress in the system of advanced training of research and teaching staff in Ukraine in the 1970s – early 21st century, which included theoretical and methodological bases of research in the last quarter of the 1970s – early 21st century; direction of research; level of research development; research methods; scientific achievements in the direction of the development of the system of advanced training of research and teaching staff of higher education institutions in Ukraine in the 1970s – early 21st century; institutional design of the results of their own research. The peculiarity of the proposed criteria is that well-founded criteria and relevant indicators allowed determining the real state of the progress in the system of advanced training of research and teaching staff in Ukraine in the 1970s – early 21st century. The results of the current research will be interesting for scientists who carry out investigations on the question of professional development of research and teaching staff of higher education institutions.